Noninvasive ventilation via bilevel positive airway pressure improved sleep in a child with congenital central hypoventilation syndrome: A case report. Issue 10 (20th October 2022) - Yang, Liqiang; Qiu, Shuyao; Zhong, Jianwen; Liu, Dabo
Abstract: We report the polysomnography findings of a 2‐year‐old girl who was previously diagnosed with CCHS and treated with bilevel positive airway pressure (BiPAP) and O2 supplementation for a year. The girl had convulsions 2 times in the last 10 days. After we replaced her nasal cannula with a nasal mask and adjusted the parameters of the BiPAP, her sleep and ventilation were improved. The polysomnographies measured under spontaneous breathing without oxygen supplementation showed that her sleep structure, heart rate, and oxygen saturation during sleep were improved 1 month and 1 year after effective BiPAP treatment.